Anti-obesity effect of simvastatin and omega-3 and its combination on obese model male Wistar rats: Effect of simvastatin, omega-3 and their combination on UCP1 - ALJuboury, Rasha Abdullatif; Al-Shawi, Nada N (Iraqi Journal of Pharmaceutical Sciences, 2022)
Strategies to reduce obesity have become main priority for many health institution and health staff around the world, as the prevalence of obesity has risen and exacerbated in most of the world mainly because of the modern life style which tend to be more sedentary with an increase eating unhealthy fast western food. Many years ago, the lipid-lowering drug simvastatin; and omega-3 were considered as a traditional lipid-lowering drug that have been well-documented to possess anti-inflammatory, cardioprotective and triglyceride-lowering properties; and their co-administration may demonstrate a complementary effect in lowering patients' triglycerides and total cholesterol to treat atherosclerosis. Many previous studies have been found other beneficial effects for simvastatin, and omega-3; since, simvastatin can be used for the treatment of Alzheimer's disease; and for prevention of prostate cancer; while omega 3 can reduce the risk of sudden cardiac death in addition to preventing obesity that has been documented by recent studies. But, the effect of simvastatin alone or its combination with omega-3 as potential anti-obesity therapy and /or protection against obesity is not yet known through their effects on thermogenic factors. Aim of the study is to evaluate the effect of simvastatin on thermogenic genes including (UCP1) using quantitative real time PCR, while the expression of uncoupling protein 1 (UCP1) protein was detected in iBAT and iWAT adipocyte by immunohistochemistry. Method One hundred twenty (120) male Wistar rats (five-six week age and weighing 100-150g) were allocated into five groups: treated with two different doses of simvastatin, omega-3 and mixed treatment, in addition to high fat diet group which considered as a control group. Treatments were given for eight weeks. Three rats from each group were weekly-authenticated along the 60 days interscapular brown adipose tissue (iBAT) and inguinal white adipose tissues (iWAT) were obtained. Results; showed that simvastatin and omega-3 have an obvious activation of UCP1genes, this reflects an increase in thermogenic process in adipose tissue in obese high fat diet rats and their combination exert a synergistic increase in the thermogenic mechanism when compared to simvastatin 9mg/ kg /day alone. Conclusion this study gives a hope for the utilization of simvastatin either alone or in combination with omega-3 as anti-obesity therapy; through their enhancement of thermogenic in white and brown adipose tissues with a consequent weight loss.